IMPLEMENTASI PROGRAM LAYANAN DUKUNGAN PSIKOSOSIAL (LDP) DALAM UPAYA MENGURANGI BEBAN PSIKOLOGIS DAN TRAUMA HEALING PADA ANAK KORBAN COVID-19: (Studi pada UPT Pelayanan Sosial Bina Remaja Blitar) - Riska Andistyani; Haryono Bambang Santoso; Rozikin Mochammad (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The Psychosocial Support Service (LDP) is a peogram aimed at children whose parents have died due to Covid-19. This program is expected to be able to reduce the symptoms of trauma in children which can lead to psychosocial disorders, help children to identify psychosocial problems, facilitate children to get acces to psychosocial services. Psychosocial Support Services (LDP) is one of the specific approaches implemented by Kementerian Sosial as an implementation of Lae Number 11 of 2009 concerning Social Welfare, Law Number 7 of 2012 concerning Social Conflict Management and Law Number 23 of 2015 on Regional Government.